Hydrothermal transforming phase structure and chemical composition of V2O5 for elevating electrochemical property of zinc ion batteries - Triosod, Sureerat; Phakkhawan, Authit; Phumuen, Phatcharin; Wanabut, Wassana; Chanlek, Narong; Kumnorkaew, Pisist; Klangtakai, Pawinee; Srepusharawoot, Pornjuk; Jarernboon, Wirat; Puttharugsa, Chokchai; Thongnum, Anusit; Chompoosor, Apiwat; et al. (My University, 2024)
V2O5 was hydrothermally modified in NaOH or KOH solutions at 180 °C for 24 h. The NaOH-modified powders had a nanorod-like structure with a crystal structure matching Na2V6O16·nH2O. The TG/DTA results of Na2V6O16·nH2O powders show a mass reduction of 4.24 % at 300 °C, corresponding to n of 1.496. KOH-modified powders have large rods and irregular structures with a crystal structure matching KV3O8. Its TG/DTA spectrum shows a very small percentage change, just 0.37 % at 600 °C. Cyclic voltammetry (CV) curves of a Na2V6O16·nH2O cathode in a 2 M ZnSO4 electrolyte exhibit higher oxidation and reduction current densities than those of pure V2O5 and KV3O8 electrodes.The best capacity of a Na2V6O16·nH2O electrode is 296.10 mAh g-1 at a current density of 50 mA g−1, which is higher than those of pure V2O5 (102.90 mAh g-1) and KV3O8 (91.07 mAh g-1) electrodes. EDS and XPS results reveal that the charge and discharge states involve de-insertion and insertion of Zn2+ ions out of/into the electrodes. Computational analysis of Zn intercalation into V2O5, Na2V6O16·nH2O, and KV3O8 structures displays increasing electron density on neighboring V atoms, which explains the increasing V4+/V5+ ratio in the discharged state as evidenced by XPS spectra.
Keywords: Hydrothermal; KV3O8; Na2V6O16·nH2O; V2O5; Zn-ion battery